Human Sovereignty Eclipsed? Toward a Posthumanist Reading of the Traumatized Subject in J.M. Coetzee’s Disgrace - İbrişim, Deniz Gündoğan (European review (Chichester, England), 2021)
The main aim of this article is to analyse J.M. Coetzee’s Disgrace (1999) from a posthumanist perspective. By focusing on the character David Lurie, this article analyses the complex materiality of bodies and the agentic powers of nonhuman entities in coping with individual trauma, where agency is no longer considered to be the distinguishing quality unique to humans. In so doing, it highlights the interdependence of the human and the nonhuman and the idea that environment is not a mere canvas onto which characters’ traumas are being reflected. On the contrary, it is a material-affective matrix which becomes a catalyst for making sense of the world in post-apartheid South Africa. At the same time, as this article argues, it decentres the sovereignty of the human subject.